Oral Interpersonal Communication in Indonesian Language Learning in Elementary Schools - Febriani, Diva; Sutama, S; Adnan, Mazlini (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study explores oral interpersonal communication within Indonesian language learning in the digital era at the elementary level, specifically aiming to examine the nature of active interaction between teachers and students and to describe how students’ argumentative abilities develop during Indonesian lessons. Methodology: Employing a qualitative ethnographic design, the research was conducted at Integrated Islamic Primary School Muhammadiyah Al‑Kautsar. Participants included the principal, the Indonesian language teacher, and grade V students. Data were collected through in‑depth interviews with educators and administrators, participatory classroom and social‑environment observations, and analysis of relevant documents. To ensure validity, multiple data sources were triangulated, and reliability was maintained by applying consistent procedural steps. Data analysis followed an inductive approach, identifying emergent patterns and insights into interpersonal communication practices. Results: Findings indicate that teachers’ oral interpersonal communication skills are pivotal in fostering students’ critical thinking and social competencies. Active, bidirectional interactions—both during classroom instruction and in students’ broader social contexts— were observed to be well integrated into Indonesian language lessons. Moreover, activities designed to engage students in argumentative discourse significantly bolstered their confidence and communicative abilities, leading to more effective learning outcomes. Applications/Originality/Value: By highlighting the foundational role of oral interpersonal communication in developing critical thinking and argumentation skills, this study offers practical strategies for optimizing teacher‑student and peer interactions in digitally enriched learning environments. Its insights can guide curriculum designers and educators in elementary settings to leverage ethnographic methods and targeted communicative activities, thereby enhancing student engagement and language proficiency in the digital era.